An investigation into the co-producers of preferred strategic behaviour in small, micro and medium tourism enterprises in South Africa - Tassiopoulos, Dimitri (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Business Management))--University of Stellenbosch, 2010.